2008
DOI: 10.1080/0972060x.2008.10643617
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition of the Fruits ofAmomum subulatumRoxb

Abstract: Hydro-distilled essential oil obtained from fruits of Amomum subulatum was characterized by a high proportion of monoterpenes (ca 90 %). The main monoterpenes were 1,8cineole (77.4 %), β-myrcene (5.0 %), α-terpineol (4.9 %) and terpinen-4-ol (2.3 %). Sesquiterpenic constituents amounting to only 2.7 % were represented by t-caryophyllene (2.3 %) and its oxide (0.4 %). A high proportion 1,8-cineole present in the oil lends it a harsh eucalyptol smell and warrants its use as substitute of true cardamon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The result indicates that the antioxidant activity of Sample B was found quit higher than Sample A whereas lesser than that of ascorbic acid. The result obtained here is well supported by the previous studied [17][18][19][20][21].…”
Section: Radical Scavenging Activity (%)=(A O −A S /A O )×100supporting
confidence: 82%
“…The result indicates that the antioxidant activity of Sample B was found quit higher than Sample A whereas lesser than that of ascorbic acid. The result obtained here is well supported by the previous studied [17][18][19][20][21].…”
Section: Radical Scavenging Activity (%)=(A O −A S /A O )×100supporting
confidence: 82%
“…It has been reported that in the chemical composition of different species of cardamoms, monoterpenes are the main compounds [ 14 , 17 , 20 , 21 , 22 ]. Also, antimicrobial activity of the cardamoms is reported [ 23 , 24 ]. On black cardamom, 1,8-cineole is the main component [ 15 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to lack of technological errors, the essential oil of the plant or bioactive compound of the particular cultivars (Seremna, Sawney, and Varlangy) has not been tested earlier. Several authors considered, the environmental conditions, e.g., type and composition of the soil (edaphic), geographic and genetic variations are the determinant factors influence the secondary metabolites of the essential oils [12][13][14]. Keeping the view in mind for cardamom pharmacological properties, we have studied the Seremna, Sawney, and Varlangy essential oils by gas chromatography-mass spectrometry (GC-MS) and also observed the effect of their essential oils for antifungal and antibacterial activities collected from Sikkim.…”
Section: Introductionmentioning
confidence: 99%